Propuesta de una política de incentivos para la acreditación de las IPS en Colombia (2018)
Users who access health services in Colombia seek that the Health Care Providing Institutions attend to their needs and expectations, through a humane and safe service; when such characteristics are not perceived, complaints about dissatisfaction come about before the governmental bodies. The unique accreditation system, offers superior quality standards that would have a positive impact on this problem, however, most Health Care Providing Institutions in Colombia do not adopt it. The general objective of the research carried out considers the proposal of an incentives policy for the accreditation of Health Care Providing Institutions in Colombia, based on the analysis of the factors that influence the decision to be accredited and the evaluation of the incentives provided by the Government for this purpose. The information was collected through a survey directed to both non-accredited and accredited and through semi-structured interviews with experts in accreditation. The proposed sampling strategy consisted of a two-stage sampling, which allows obtaining a low margin of error and inference to the entire Health Care Providing Institutions population of the country and by area. The response of 254 Health Care Providing Institutions was achieved. It was concluded that both the Health Care Providing Institutions and the accreditation experts consider that accreditation can become a strategy for compliance with organizational goals, improvement in the provision of health services and increase in user satisfaction and the granting of institutional prestige